(Re)Production of Knowledge for Human Resource Building: The Multicultural Dynamics of the Indonesian-language Wikipedia - Christopher Allen Woodrich (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Access to information is a fundamental requirement for developing quality humanresources. One prominent source of such information is Wikipedia, a website whichadvertises itself as "the free encyclopedia that anyone can edit". This paper, which isbased on participatory action, observational, and library research conducted over aperiod of ten years, describes the multicultural dynamics of the Indonesian-languageWikipedia (WPID) after first situating it within the context of the global Wikimediamovement. Established in 2003, WPID freely (in both the libre and gratis sense) offersmore than 380,000 articles with a wide range of information which can be used forhuman resources building. Its more than 2,200 active users, originating from variedbackgrounds, (re)produce knowledge through several means, including writing originaltext based on their understandings of existing sources and translating articles which existon other Wikipedias. This combination of actors, approaches, and content has led tocomplex interactions between the (primarily Western) culture of the global Wikimediamovement, the mixed cultures of source articles, and the Indonesian/local cultures of theactors. This article argues that WPID has organically negotiated a compromise betweenthese at times conflicting cultural dynamics to create a hybrid source of information.Keywords: Crowdsourcing, knowledge production, knowledge reproduction, Wikipedia